Evaluation of the mycotherapeutic potential of pleurotus ostreatus i-fraction in breast cancer - Alonso, Eliana Noelia (2021)
Mycotherapy is one of the most promising complementary and integrative approaches in cancer care. Mushrooms compounds have been shown to exert antitumoral activity stimulating the immune system and modulating signaling pathways or cellular capabilities aberrantly-activated in cancer. Previously, we demonstrated the antitumoral and antimetastatic activity of Grifola frondosa D-Fraction in breast cancer, in vitro and in vivo. Recently, we have also focused on edible mushrooms cultivated in Argentina. In this context, the purpose of the current study is to evaluate the antitumoral potential in breast cancer of Pleurotus ostreatus I-Fraction, an extract of water-soluble polysaccharides obtained from the fruiting body. We found that I-Fraction decreased the viability of 4T1 cells mammary adenocarcinoma (triple-negative, murine) in a concentration and time-dependent manner (24 and 48 h; p < 0.001). In addition, I-Fraction (2.5 mg/mL, 48 h) increased the number of 4T1 cells in the subG0/G1 phase (p < 0.001) and decreased those in the G0/G1 phase compared to vehicle (p < 0.001). These results suggest that I-Fraction decreases 4T1 cell viability through an induction in cell death. In addition, we found that I-Fraction decreased migratory (p < 0.01) and invasive (p < 0.001) capability of 4T1 cells at 13 h of treatment, compared to vehicle. In conclusion, these results demonstrate the mycotherapeutic antitumoral potential of P. ostreatus I-Fraction on 4T1 breast cancer cells